Variação longitudinal e radial da densidade básica do lenho de eucalipto considerando os anéis anuais de crescimento - Lima, Rebeca Alves Barreto (2018)
Knowledge of wood properties and characteristics, as well as its variations, is important to define the most suitable uses. The variability of characteristics within the structure of tree annual growth rings is still little explored and can be determinant in the wood use. Such rings are reflections of plant growth year by year and should be evaluated to identify if they have a defined variation pattern of a given characteristic in the stem, both longitudinally and radially. This study aimed to adjust the general model of radial and longitudinal variation pattern of the wood basic density based on the information contained in the tree annual growth rings; determine which annual growth ring estimates the average basic density of the tree and; to obtain a map of variation of the wood basic density inside the stem. Two hybrids clones of Eucalyptus urophylla x E. grandis were used and three trees were sampled by genetic material. The clones are from 10-year-old settlement, located in the municipality of Luminárias-MG. The sampling consisted in the removal of discs along of tree stem at longitudinal positions of the base (0.3m), DBH (1.3m) and every 2m until 23.3m high. In each longitudinal sampling position, three 3 cm thick discs were removed, the first to obtain the disk basic density, the second to identify the annual growth rings and determine their basic density (BD) and the third was left as a reserve. The trees were cubed and the Smalian equation was used to calculate the individual volume. Annual growth ring BD was determined by maximum moisture content method. The SURFER 15 software was used to obtain the variation map of BD by individual tree and clone. Regression analysis, simple and multiple linear models, was used to adjust equations defining the radial and longitudinal variation pattern of BD, considering the structure of annual growth rings per clone evaluated. Correlation analysis was used to identify associations between the annual growth ring BD with average BD by longitudinal sampling position, between the disc BD and annual growth rings BD and between average BD of the tree obtained by discs and annual growth rings. The results showed that it was not possible to estimate a general model to represents the variation pattern, both radial and longitudinal. Considering the smaller longitudinal positions to facilitate sampling, to the clone A the 10th annual growth ring BD at 1.3m of height presented the highest significant correlation with average BD of the tree obtained with the annual growth rings, while for clone B it was the 9th ring at that same height (1.3m). Greater magnitude correlation between the annual growth ring BD with the average BD of the tree estimated by discs was at the longitudinal position of 1.3m in the 8th and 9th annual growth ring, for clone A, and at 9.3m in the 2nd annual growth ring, for clone B.